POST-MAINTENANCE FLIGHT TEST AS A MECHANISM OF MOTION IN MIRCE MECHANICS - Knežević, Jezdimir (Journal of Applied Engineering Science, 2018)
MIRCE Mechanics is a part of MIRCE Science that focuses on the scientific understanding and description of the physical phenomena and human rules that govern the motion of functionable system types though MIRCE Space[1]. A full understanding of the mechanisms that influence this motion through MIRCE Space is essential for accurately predicting the functionability performance of functionable system types using MIRCE Science. According to the 5th axiom of MIRCE Science, the probability that a completed maintenance task introduces faults or errors is greater than zero. To reduce the probability of introducing undetected maintenance errors and their consequential impact on the system operational process, the concept of the Post-Maintenance Flight Tests (PMFT) is used in aviation industry. Consequently, the main objective of this paper is to critically assess these types of maintenance verification tests and their impact efficacy on the functionability performance, as understood through the application of MIRCE Science. The physical reality of inducing errors during maintenance and their consequences on post-maintenance flight is illustrated using an incident that regrettably took the lives of two pilots, when their Piper PA 46-350P, N962DA, crashed into the Spokane River on May 7, 2015, following an attempted landing at Felts Field Airport in Spokane, Washington, USA